Efektivitas Manajemen Kurikulum Merdeka Belajar dalam Meningkatkan Kinerja Tenaga Pendidik di UPT SMP Negeri 6 Medan - Kenara (UIN Mahmud Yunus Batusangkar, 2025)
This study examines the effectiveness of Merdeka Learning Curriculum management in improving the performance of educators at UPT SMP Negeri 6 Medan. The implementation of the Merdeka Learning Curriculum aims to enhance the quality of education through a more flexible, innovative, and student-centered learning process. The purpose of this study is to determine the extent to which the management of the Merdeka Learning Curriculum is effective in improving the performance of educators at UPT SMP Negeri 6 Medan. This study employs a qualitative approach with a descriptive method. The research was conducted at UPT SMP Negeri 6 Medan. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out through the stages of data collection, data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and method triangulation. The results of the study indicate that: (1) planning of the Merdeka Curriculum is conducted through meetings and teacher discussion forums, preparation of teaching schedules, non-cognitive assessments, teacher training, and the development of teaching modules and project modules; (2) curriculum implementation is carried out through intrakurricular learning, extracurricular activities, and the Pancasila Student Profile Strengthening Project; (3) curriculum organization includes the regulation of learning loads, graduation criteria, and the academic calendar; (4) evaluation is conducted through input evaluation, process evaluation, learning evaluation, as well as school operational curriculum and program evaluation; and (5) curriculum audits are carried out through teacher reflection, cognitive assessments for teachers and students, supervision by the principal, and the utilization of the Merdeka Teaching Platform (PMM).